Use of Natural Agents and Agrifood Wastes for the Treatment of Skin Photoaging - Melania Parisi; Mariavittoria Verrillo; Maria Antonietta Luciano; Giuseppina Caiazzo; Maria Quaranta; Francesco Scognamiglio; Vincenzo Di Meo; Alessia Villani; Mariateresa Cantelli; Lucia Gallo; Giovanna Giuseppina Altobelli; Serena Poggi; et al. (2023)
Photoaging is the premature aging of the skin caused by repeated exposure to ultraviolet (UV) rays. The harmful effects of UV rays—from the sun or from artificial sources—alter normal skin structures and cause visible damage, especially in the most exposed areas. Fighting premature aging is one of the most important challenges of the medical landscape. Additionally, consumers are looking for care products that offer multiple benefits with reduced environmental and economic impact. The growing requests for bioactive compounds from aromatic plants for pharmaceutical and cosmetic applications have to find new sustainable methods to increase the effectiveness of new active formulations derived from eco-compatible technologies. The principle of sustainable practices and the circular economy favor the use of bioactive components derived from recycled biomass. The guidelines of the European Commission support the reuse of various types of organic biomass and organic waste, thus transforming waste management problems into economic opportunities. This review aims to elucidate the main mechanisms of photoaging and how these can be managed using natural renewable sources and specific bioactive derivatives, such as humic extracts from recycled organic biomass, as potential new actors in modern medicine.